Intellectual capital of the enterprise: nature and modern approaches to evaluation - Aimukhanbetova , G. (BUKETOV BUSINESS REVIEW, 2018)
The article reveals the concept of the intellectual capital of an enterprise, which is one of the main factors in the development and enhancement of the enterprise's competitiveness in modern conditions. It is considered various approaches to the concept of intellectual capital, which is often called the «invisible asset», which emphasizes the intangible nature of the constituent components. The main differences between intellectual capital and intangible assets of the enterprise are considered. The authors consider the main elements of intellectual capital: human capital; organizational capital; capital of relations; emotional capital. The article reveals the approaches to the evaluation of intellectual capital, which allows to take into account intangible assets of the enterprise, thanks to which it is possible to fairly estimate the value of the organization; discover reserves and development factors; increase innovation and competitiveness of the enterprise. Approaches to evaluation of intellectual capital are given taking into account its constituent elements, their internal interaction, and also their classification.The application of D. Tobin's methodology for estimating costs for creating the intellectual capital of an enterprise is considered. The method of intellectual added value of A. Pulik considering three enterprise indicators is considered: the added value of physical capital; the added value of human capital; added value of structural capital.